Supporting the Performance and Efficiency of Governance – Expediency Control and Performance Measurement in SAI’s Audit - Domokos, László; Németh, Erzsébet; Jakovác, Katalin (Public Governance, Administration and Finances Law Review, 2016)
The main goal of the management of public funds and public assets is to promote social well-being. In order to realize this main goal and to evaluate individual measures, it is indispensable to sub-categorize the primary objective, determine the hierarchy of objectives, assign measurable criteria to the objectives, evaluate performance, and provide feedback. By performing objective, professionally-sound evaluations and providing feedback, independent audits contribute significantly to the improvement of performance. A basic requirement of all audits, however, is the auditability of the objective’s implementation and effectiveness, and the definition of performance criteria for each objective. A large part of the proven methods and tools used in the for-profit sector for performance assessment can be applied successfully at organizations of the public sector as well. The audit findings of the State Audit Office of Hungary (SAO) confirm that the management and control systems of both public entities and state-owned enterprises need to be improved significantly in order to ensure good governance and public sector management. Indicators that capture and adequately measure the effectiveness and efficiency of public spending are important prerequisites for the efficient management of public funds and for the planning process.